The Relationship of Demographic Characteristics to The Community Knowledge about Dapatkan, Gunakan, Simpan, Buang (Dagusibu) Fever Medicine - Eny Hastuti; Syahrizal Ramadhani; Cast Torizellia; Norlita Alyatri (Lambung Mangkurat, 2021)
DAGUSIBU medicine is a health education program created by The Indonesian Pharmacists Association (Asosiasi Apoteker Indonesia, IAI) in an effort to realize Gerakan Keluarga Sadar Obat (GKSO). DAGUSIBU medicine stands for DApatkan, GUnakan, SImpan, BUang obat. The purpose of this study was to determine the demographic characteristics and the relationship of demographic characteristics to the level of public knowledge about DAGUSIBU fever medicine. The design of this research is observational analytic using approach cross-sectional. The sample is 138 people with purposive sampling. The instrument used is a questionnaire, analyzed by univariate and bivariate analysis using test Chi-Square. The results showed that the majority of respondents were in adulthood (33.3%), female (59.4%), basic education background (64.5%), working status (75.4%), never received information (78.3%) and the level of knowledge in the less category (47.8%). The results of statistical tests showed p-value= 0.003, gender (0.0001), education level (0.0002), occupation (0.001) and had/never received information (0.0001). The conclusion in this study was that the majority of the respondents were of adult age, female, with basic education background, never received information and the level of knowledge was less category and there was a significant relationship between demographic characteristics and the level of public knowledge.